2013
DOI: 10.12714/egejfas.2013.30.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition of the five deep sea fish from the Aegean Sea.

Abstract: Ege Denizi'nde bulunan beş derin deniz balığı: Argentina sphyraena, Glossanodon leioglossus, Chlorophthalmus agassizi, Hoplostethus mediterraneus ve Capros aper 2003 bahar mevsimi süresince ticari trol balıkçıları tarafından hedef dışı av olarak elde edilen örnekler olarak çalışılmıştır. Türlerin besin kompozisyonlarını belirlemek için mide içerikleri incelenmiştir ve türlerin trofik durumlarının özellikle karnivor seviyede yer aldığı görülmüştür. Beş predator türün besin kompozisyonunda iki esas av grubu bulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
(32 reference statements)
2
5
0
Order By: Relevance
“…This result is generally consistent with the findings of other authors focusing on the Atlantic (Fock et al 2002, Lopes et al 2006, in the central Tyrrhenian Sea (Carpentieri et al 2016), in the western Mediterranean (MacPherson 1979) and in the eastern Mediterranean (Sever et al 2013). Santos and Borges (2001) found that Euphausiacea and Amphipoda were the main prey of C. aper in the southern coast of Portugal.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…This result is generally consistent with the findings of other authors focusing on the Atlantic (Fock et al 2002, Lopes et al 2006, in the central Tyrrhenian Sea (Carpentieri et al 2016), in the western Mediterranean (MacPherson 1979) and in the eastern Mediterranean (Sever et al 2013). Santos and Borges (2001) found that Euphausiacea and Amphipoda were the main prey of C. aper in the southern coast of Portugal.…”
supporting
confidence: 93%
“…Similar results, with the vacuity index near to zero, have been reported by Fock et al (2002). As opposed, Sever et al (2013) found a high degree of empty guts. Carpentieri et al (2016) indicated that the species shows a marked daily temporal pattern, with feeding peak during daylight hours.…”
supporting
confidence: 89%
See 3 more Smart Citations